The Role of Government Agencies on Product Safety in the Nigerian Pharmaceutical Sector: A Conceptual View - Chikaodi; U. ORANUSI; Omotayo A. ADEGBUYI; Ebeguki E. IGBINOBA; Oluwakemi T. OREAGBA (Communications of International Proceedings, 2021)
The government’s regulation on product safety is to protect the consumer by eliminating injuries at home, market place and as well as to educate consumers on product safety measures through guidelines and warnings. However, the product safety of pharmaceutical industries remains a major challenge in the developing countries such as Nigeria. The paper therefore evaluates the role of government agencies on product safety of pharmaceutical industries in Nigeria. A conceptual review of extant literature was adopted. Based on the conceptual, empirical and theoretical review, Findings revealed that many losses of life and damage to health occur as a result of product failures.  it was concluded that there is need to secure and achieve good product safety standard so as to make sure that consumers are well secured..
Keywords: Government Agency; Pharmaceutical Industry; Government Role; Product Safety.